Outcomes of Medical Education in Nepal - Reddy, V. Devendar; Upadhayay, N; Yadav, SK; Subedi, B (Journal of Gandaki Medical College-Nepal, 2017)
The standards of medical education in Nepal and other countries in Asia are improving gradually. The medical education is appeared to be student centered. But a teacher is also responsible to improve the academic standards and overall performance of the students. There is a need to provide short period of practical vocational training to teachers in the subject of their specialty. A better teacher trains the student in a better way than untrained medical personnel. In any class, the students are the best judges, so teachers should get a feedback from students after the class and it leads to better performance by a teacher in future classes. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, Page: 63-64